Author Correction: Selective 6H-SiC White Light Emission by Picosecond Laser Direct Writing - Sicong Wang (Nature Portfolio, 2018)
A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has not been fixed in the paper.